THE DEVELOPMENT OF AN INOVATION MANAGEMENT MODEL USING THE PROFESSINAL LEARNING COMMUNITY (PLC) APPORACH FOR TEACHER AT METTASUKSA SCHOOL UNDER THE ROYAL PATRONAGE - Pangchan, Pakpoom; Sirikulapan, Chatchai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2025)
This research has the following objectives: 1) Study the innovation management conditions of teachers at Metta Suksa School. 2) Create an innovation management model using the (PLC) principle 3) Experiment with the innovation management model using the (PLC) principle 4) Evaluate the results of using the innovation management model using the (PLC) principle The experimental group consisted of 15 teachers at Metta Suksa School. The research instruments were: 1) PNI Needs Index Questionnaire 2) Expert Opinion Questionnaire using the Delphi technique 3. Evaluation form before and after using the innovation management model Statistics used 1) PNI Needs Index 2) Confirmation of the model with Medium and IQR. 3) Find the reliability of Cronbach’s 4) Test the hypothesis with a pair sample t-test. The research results found that: 1) The innovation management conditions of teachers at Metta Suksa School. The study of the needs is in the aspect of using and developing innovative media. The value (PNI) = 0.647 2) Creating an innovation management model using the (PLC) principle 1) Study data to create a model 2) Confirm the model with the Delphi Technique The analysis result has an IQR value = 0. The experts have a consensus opinion. And the model is correct and can be used in the experiment. 3) The model was tested with an experimental group of 15 people, with pre- and post-tests. The overall experimental results, 𝑥̅ = 4.59, SD. = 0.425, p-value=.01**, indicate that the model is effective in managing teachers’ innovation with a statistical significance of .01**. 4) The model evaluation results of the experimental group before and after using the model were statistically significantly different at .01**, which is in line with research hypothesis 1, and the evaluation of teachers’ satisfaction after using the model was at the highest level.